So you've been publicly shamed - Ronson, Jon 1967- (Picador, 2015)
"From the internationally bestselling author of The Psychopath Test, a captivating and brilliant exploration of one of our world's most overlooked forces. For the past three years, Jon Ronson has been immersing himself in the world of modern-day public shaming-meeting famous shamees, shamers, and bystanders who have been impacted. This is the perfect time for a modern-day Scarlet Letter-a radically empathetic book about public shaming, and about shaming as a form of social control. It has become such a big part of our lives it has begun to feel weird and empty when there isn't anyone to be furious about. Whole careers are being ruined by one mistake. A transgression is revealed. Our collective outrage at it has the force of a hurricane. Then we all quickly forget about it and move on to the next one, and it doesn't cross our minds to wonder if the shamed person is okay or in ruins. What's it doing to them? What's it doing to us? Ronson's book is a powerful, funny, unique, and very humane dispatch from the frontline, in the escalating war on human nature and its flaws"..